Impact of Introducing Routine Antenatal Ultrasound Services on Reproductive Health Indicators in Mpigi District, Central Uganda. Issue 4 (December 2015) - Kawooya, Michael G.; Nathan, Robert O.; Swanson, Jonathan; Swanson, David L.; Namulema, Edith; Ankunda, Racheal; Kirumira, Fred; Ddungu-Matovu, Peter
Abstract : Abstract: The preponderance of global maternal and neonatal deaths occurs in low-resource countries. The risk factors that lead to these deaths are often detectable with ultrasound (US) and potentially preventable. We assessed the impact of performing US scanning during antenatal care (ANC) on reproductive health service utilization in a rural Ugandan district. This pragmatic comparative study was conducted in 2 constituencies of Mpigi district in Uganda. In the 5 intervention sites located in the Mawokota North constituency, facility midwives were trained in limited obstetric US scanning. They were equipped with solar-powered portable US machines and redeployed to offer US scanning as an integral component of ANC. The 5 control sites in the Mawokota South constituency offered the same ANC services without US scanning. We compared the difference in the first and fourth ANC attendance, facility deliveries, and referral of obstetric complications in the intervention and the control sites before and after the introduction of US. There was a 32% increase in the first ANC attendance at the intervention sites compared with 7.4% in the controls sites ( P < 0.001). In the intervention sites, the fourth antenatal attendance increased by 147% compared with 0.6% decline in the control sites ( P < 0.001). Referrals of high-risk pregnancies increased by 40.7% in the intervention sites compared with 25% in the control site. The number of births at the interventional sites increased by 34.1% compared with 29.5% in the control sites. Integration of limited obstetric US into routine ANC visits is associated with an increase in ANC attendance.